Impact of the Russian Invasion on Mental Health of Adolescents in Ukraine - Olga Osokina; Sanju Silwal; Tatiana Bohdanova; Matthew Hodes; Andre Sourander; Norbert Skokauskas (United States, 2022)
Objective
Very limited evidence is available on the psychological impact of war on adolescents in Ukraine. This study compared war experiences and posttraumatic stress disorder (PTSD), anxiety and depression in adolescents living in war-torn and peaceful regions of Ukraine, more than 2 years after Russia first invaded in 2014.
Method
The cross-sectional study included 2,766 students aged 11-17 years living in the war-torn Donetsk region and in Kirovograd in central Ukraine. Self-reported PTSD, depression, and anxiety were assessed by Harvard Trauma Questionnaire, Patient Health Questionnaire-9, and Generalized Anxiety Disorder-7. Data were collected from September 2016 to January 2017. Binary and multinomial logistic regression models were used to examine the association between PTSD, anxiety, and depression and regions.
Results
War trauma and daily stress were higher in adolescents in the Donetsk region; 881 (60.2%) adolescents had witnessed armed attacks, 204 (13.9%) were victims of violence, and 409 (27.9%) were forced to leave their homes. They also had significantly increased risks for PTSD (odds ratio [OR] 4.11, 95% CI 2.37-7.13), severe anxiety (OR 3.10, 95% CI 1.83-5.27), and moderately severe/severe depression (OR 2.65, 95% CI 1.79-3.92).
Conclusion
Traumatic events and daily stress were strongly associated with psychological distress in adolescents living in a war-torn region in Ukraine. These findings can help in understanding, measuring, and addressing the long-term impact that the current escalating war in Ukraine will have on adolescents’ mental health and social functioning.